2016
DOI: 10.3847/0004-637x/817/1/18
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Removal of Exomoons During Planetary Migration

Abstract: Jupiter and Saturn play host to an impressive array of satellites, making it reasonable to suspect that similar systems of moons might exist around giant extrasolar planets. Furthermore, a significant population of such planets is known to reside at distances of several Astronomical Units (AU), leading to speculation that some moons thereof might support liquid water on their surfaces. However, giant planets are thought to undergo inward migration within their natal protoplanetary disks, suggesting that gas gi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 55 publications
2
52
0
Order By: Relevance
“…For instance, the perturbations experienced by a moon during its evolution could drive its disruption or escape. Thus, in the host-planet migration phase, the moon can either be ejected via "evection resonance" (Spalding, Batygin & Adams 2016) or by planet-planet scattering (Gong et al 2013;Hong et al 2018). As a result, when the moon-planet system reaches its final configuration in a close-in orbit (Namouni 2010), the tidal interplay with the planet and the star would push the moon towards large circumplanetary orbits where it can be perturbed and lost (Alvarado-Montes, .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the perturbations experienced by a moon during its evolution could drive its disruption or escape. Thus, in the host-planet migration phase, the moon can either be ejected via "evection resonance" (Spalding, Batygin & Adams 2016) or by planet-planet scattering (Gong et al 2013;Hong et al 2018). As a result, when the moon-planet system reaches its final configuration in a close-in orbit (Namouni 2010), the tidal interplay with the planet and the star would push the moon towards large circumplanetary orbits where it can be perturbed and lost (Alvarado-Montes, .…”
Section: Introductionmentioning
confidence: 99%
“…The Hill stability criterion, Roche limit, stellar tidal stripping, tidal decay, planet migration, direct planet perturbation, and planetary close encounters are among the mechanisms that can destabilize the orbits of exomoons (Barnes & O'Brien 2002;Domingos et al 2006;Donnison 2010;Frouard & Yokoyama 2013;Holman & Wiegert 1999;Kane 2017;Payne et al 2013;Sasaki et al 2012;Namouni 2010;Spalding et al 2016). The stability of distant satellites (a s > 0.1 R H ), which would be classified as irregular satellites in the Solar System, in planet-planet scattering, are investigated by Gong et al (2013) and Nesvorný et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…This resonance was first studied in the context of the Moon-Earth-Sun system by Touma & Wisdom (1998), who showed that the resonance between the Moon's orbital precession due to the Earth's oblateness and the periodic perturbation of the Sun could give the Moon a significant eccentricity in its early evolution, which later produce the misalignment of the Moon's orbit. Recently, Spalding, Batygin & Adams (2016) studied the evolution of exomoons during planetary migration, and showed that evection resonance could induce eccentricity growth of exomoons, leading to their collisions with the host planet.…”
Section: Introductionmentioning
confidence: 99%